Correlation between Cardiorespiratory Fitness and Blood Pressure in Elderly - Fitri Filmasari; Farid Rahman; Young Ari Kusworo (Indonesian Journal of Medicine, 2022)
Background: Due to its strong association with major morbidity and mortality in the elderly, such as heart attack, stroke, kidney disease, and death, hypertension is currently one of the health problems associated with non-communicable diseases. It is certainly influenced by various vari¬ables, one of which is one’s cardiorespiratory fitness which can affect blood pressure. The study aims to find out if there is a correlation between cardiorespiratory fitness and blood pressure in the elderly.Subjects and Method: The cross-sectional study was conducted in Pepe Village, Kwarasan, Juwiring, Klaten, Central Java. A sample of 31 elderly people was selected by using purposive sampling. The dependent variable was blood pressure. The independent variable was cardiorespiratory fitness. Cardiorespiratory fitness was measured by the Six Minute Walking Test (SMWT). Blood pressure was measured with a sphygmomanometer. The correlation between cardiorespiratory fitness and blood pressure was tested using Pearson correlation and Spearman rho with a 95% confidence interval and p<0.050 statistical meaningfulness.Results: Cardiorespiratory fitness lowered systolic blood pressure by 0.14 mmHg (r= -0.14; p= 0.442) and diastolic blood pressure by 0.55 mmHg (r= -0.55; p= 0.771), but both were statistically insignificant.Conclusion: There was no relationship between blood pressure and physical fitness in the elderly.Keywords: hypertension, blood pressure, cardiorespiratory fitness, six-minute walking test, elderly.Correspondence: Farid Rahman. Study Program of Physiotherapy, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. Jl. Ahmad Yani, Pabelan, Kartasura, Surakarta, Central Java 57162, Indonesia. Email: Fr280@ums.ac.id. Mobile: 085223333141.Indonesian Journal of Medicine (2022), 07(04): 379-386https://doi.org/10.26911/theijmed.2022.07.04.03